Meningkatkan hasil belajar menggunakan metode make a match pada mata pelajaran pendidikan agama islam di SMPIT El Ma’mur Kota Bogor - Fadil, Khaidir; Hakim, Fariq; Rusmana, Indriya (Jurnal Pendidik Indonesia, 2024)
Islamic education today is still faced with various challenges, one of which is the ineffective implementation of teaching methods. Based on preliminary studies conducted at SMP IT eL Ma’mur Kota Bogor, it was found that students' learning outcomes were low due to monotonous and less varied classroom instruction. This study aims to evaluate the improvement in students' learning outcomes in Islamic Education subjects and to identify obstacles in the learning process using the make a match method. The research method used is classroom action research with the Kemmis and McTaggart model conducted in two cycles, involving 29 students as the sample. The results show: 1) The implementation of the make a match method in Islamic Education learning in the eighth grade of SMP IT eL Ma’mur Kota Bogor successfully improved students' learning outcomes. In the first cycle, 15 students achieved mastery with an average score of 76, while in the second cycle, 26 students achieved mastery with an average score of 85. 2) Observations during the intervention showed a significant increase in student engagement. In the first cycle, student engagement reached 53% and had not yet achieved mastery. In the second cycle, student engagement increased drastically to 92%. These results indicate that the make a match method is effective in improving learning outcomes and student engagement in Islamic Education learning.